FRI0413 Comorbidity in a Cohort of Primary Sjögren's Syndrome Patients. (9th June 2015) - Fernandez Castro, M.; Andreu, J.L.; Rosas, J.; Martínez Taboada, V.; Olivé, A.; Sánchez-Piedra, C.; Menor, R.; Rodriguez, B.; García Aparicio, A.; Lόpez Longo, F.J.; Manrique-Arija, S.; García Vadillo, J.A.; et al.
Abstract : Background: Primary Sjögren's syndrome (pSS) is a chronic systemic autoimmune disease with a substantial impact on patient's quality of life and associated comorbidities could worsen the prognosis and complicate the management of the disease. Objectives: The aim of our study was to describe comorbidities in a Spanish cohort os pSS patients. Methods: We took advantage of a multicenter descriptive transversal study of a cohort of pSS patients fulfilling European/American criteria. It is a randomised register of patients obtained from thirty three Reumathology clinics all over Spain. The presence of comorbidities was investigated in every patient. Previous informed consent was obtained and local ethics committees approved the study. Variables were analysed by descriptive statistical methods, using means, medians, and rates, with their deviations and interquartile ranges (p25-p75). Results: A total of 437 patients were included, 95% of them women, with a median age of 58 years. Dyslipidemia was the most common comorbidity, appearing in 33% of the cases, with hypertension in second place with a prevalence of 25%. Osteoporosis was present in 18% of patients. Furthermore, 37 patients had at least an osteoporotic fracture. Seventy four patients had never smoked. Diabetes was present in 6% of cases. Less than 7% of the patients had some kind of cardiovascular event: 4 patients ischemic heart disease, 14 patients peripheral arterial disease and 15 patients strokes. Among patients with peripheral arterial disease, only one patient showed positive anti phospholipid antibodies. Thirteen patients (3%) had heart failure. Sixty four patients (14%) had fibromyalgia. Five patients (1%) had celiac disease and 2 (0.46%), multiple sclerosis. Seven lymphomas were observed, four of them MALT type and two Hogdkin's disease. Three patients developed multiple myeloma and two Waldenstrom's macroglobulinemia. Twenty one cases of other malignancy were registered. Conclusions: Primary Sjögren's syndrome's patients frequently present associated comorbidities, been dyslipidemia, arterial hypertension and osteoporosis the most prevalent. Lymphoma prevalence rate for this series is 1, 6 percent. Disclosure of Interest: None declared